The Influence 0f Transformational Leadership Style, Organizational Culture and Organizational Communication On Employee Job Satisfaction - Fitri Rezeki (Cita Konsultindo Research Center, 2023)
Employee job satisfaction is the emotional state of employees who feel comfortable or uncomfortable with their work. Employees who are very satisfied with their work show a positive attitude towards their work. Employees will enjoy their work and do their job with all their heart. This study aims to examine, examine and obtain results how the influence of Transformational Leadership Style, Organizational Culture and Organizational Communication on Job Satisfaction at UD Sumber Rezeki. The results of this study indicate that: There is a negative influence between Transformational Leadership Style on Job Satisfaction of UD Sumber Rezekiemployees. There is a positive and significant influence between Organizational Culture on Job Satisfaction of UD Sumber Rezekiemployees. There is a positive and significant effect between Organizational Communication on Employee Job Satisfaction at UD Sumber Rezeki..